MUSTAHIK ZAKAT DALAM TAFSIR AL-MISBAH (PENAFSIRAN AYAT 60 SURAT AL-TAUBAH) - FA'ATIN, SALMA (ZISWAF, 2016)
Mustahik concept of zakat in the Qur'an, verse 60 of Surat al-Tawbah, still today, the study of which is always contextual, even experiencing growth and expansion of meaning. This paper will explore the concept mustahik zakat in verse 60 of Surat al-Tawbah, specifically in the Tafsir al-Misbah, with the method of descriptive-analytic, ie digging meaning of the concept of mustahik zakat, describing exposures significance to further analyze it in the context of empowerment and management mustahik zakat. The results of this study demonstrate the potential of such a large charity, then it should be used as an instrument in economic development. Mustahik zakat, one of which is poor, it is necessary empowerment for them; First, empowerment through the development of individual attitudes (increase in work ethic, straighten understanding of religious terms-ascetic, qana'ah, trust, syukur), empowerment through the structure, the systems and the people involved in the system. Communities and governments who play an important role in the establishment of a system or structure that is more equitable so as to create prosperity, not poverty.